Szent András Fogadó marketingkoncepció tevékenységének a feltérképezése - Szabó Diána (2019)
My thesis is about the complete presentation of the Szent András Inn, the Inn's location in the territory and its sales strategy. With my thesis I would like to introduce the activities of the Inn and the tasks it has. In addition, the external environment of the organization, from which we get a picture of travel habits, is of course also presented in the internal environment. In the course of my thesis I also examined the marketing tools used by the organization to boost the region, the strengths and dangers we have to face in the Fertő region. The reason I chose this topic was because tourism marketing was the closest to me during my studies.